The statutory rape law in Malaysia: an analysis from shariah perspective - Abdullah, Nur Aina; Haneef, Sayed Sikandar Shah (2017)
This paper is critique of the Malaysian definition and punishment of statutory rape law in the Penal code from the Shariah sand point. It argues that the present statutory law is not only in line with the legal definition of adulthood from Shariah point but runs counter to its notion of criminal justice and philosophy of preventing sexual promiscuity.